The Role of Omnichannel Customer Experience in Strengthening Customer Loyalty - Rachmat Tri Yuli Yanto; Irma M Nawangwulan; Samuel PD Anantadjaya; Bekti Utomo; Antonius Ary Setyawan (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to examine the role of omnichannel customer experience in strengthening customer loyalty at ETC & Foundation Bandung, an educational institution providing English learning services through multiple service channels. In the digital era, educational service providers increasingly integrate online and offline channels to improve customer experience and maintain long-term relationships with customers. This study employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through a questionnaire distributed to 100 respondents who had previously used the services of ETC & Foundation Bandung. The sampling technique used was purposive sampling, targeting customers who had interacted with the institution through at least one service channel such as WhatsApp, Instagram, website, or direct visits. The research model examines the relationships between omnichannel customer experience, customer satisfaction, and customer loyalty. The findings are expected to show that integrated and consistent customer experiences across multiple channels can enhance customer satisfaction and ultimately strengthen customer loyalty. This study contributes to the development of service marketing literature, particularly in the context of educational service institutions implementing omnichannel strategies.